Nutrien dan Morfologi Membran Kerabang Telur Ayam Kampung sebagai Bahan Baku Produksi Kolagen - Rina Wahyuningsih; Andi Febrisiantosa; Teguh Wahyono; Ahmad Iskandar Setiyawan; Diah Pratiwi; Mohammad Faiz Karimy; Taufik Kurniawan; Ragil Yuliatmo; Yuny Erwanto; Abdul Rohman (Institut Pertanian Bogor, 2024)
Collagen derived from the eggshell membrane, is an increasingly popular functional material. Native chicken is one of the leading local commodities whose industrial waste has the potential to be used as collagen raw material. This study aimed to evaluate the nutrients and morphology of the eggshell membrane of native chicken eggs as raw material for collagen production. The parameters observed were morphology using electron scanning microscopy, mineral composition, and collagen nutrient content (water and protein). SEM observations showed that the eggshell membrane of native chicken eggs was fibrous. The meshed fiber form represents the extracellular matrix present in collagen proteins. The eggshell membrane contains Cl, K, Ca, P, and Mg macrominerals at 1.696%, 1.796%, 14.30%, 0.437%, and 0.146%, respectively. Microminerals I and Mo were also found at 0.00034% and 0.00014%, respectively. The moisture content of the superior native chicken eggshell membrane decreased by 13.05% after the collagen extraction (p<0.05), with a crude protein content of 25.32% after the extraction. It was concluded that the eggshell membrane of native chicken eggs produces fibrous morphological characteristics that are meshed and contain high minerals so that they have the potential to be used as raw materials for collagen production in various applications. Keywords: collagen, eggshell, eggshell membrane, native chicken, morphology